Early Predictive Value of NT-proBNP Combined With Echocardiography in Anthracyclines Induced Cardiotoxicity - Dong, Yingjun; Wu, Qiong; Hu, Changqing (Frontiers in Surgery, 2022)
Objective: Determine the predictive value of n-terminal b-type natriuretic peptide (NT-proBNP) combined with echocardiography in the diagnosis of anthracyclines-induced chronic cardiotoxicity. Methods: A total of 80 female breast cancer patients who were admitted to our hospital from January 2019 to October 2021 were included. The 26 patients with cardiotoxic events were classified into the cardiac impairment group, and the 54 patients without cardiotoxic events were classified into the normal control group. N-terminal B-type natriuretic peptide (NT-proBNP) levels and cardiac echocardiography were measured before the start of the chemotherapy cycle, in cycle 3 of the chemotherapy, and after the chemotherapy cycle in all cases. Pearson's method was used to analyze the correlation between NT-proBNP and LVEF. The ROC curve was used to evaluate the predictive value of NT-proBNP and LVEF for cardiac toxicity events. Results: After three cycles of chemotherapy and chemotherapy, the levels of NT-proBNP in patients of the two groups were significantly higher than those before chemotherapy (P<0.05). The levels of NT-proBNP in the cardiac injury group after three cycles of chemotherapy and chemotherapy were higher than those in the normal control group at the same time point (P<0.05). The LVEF of patients in the cardiac impairment group after chemotherapy was lower than that before chemotherapy, and the LVEF after chemotherapy was lower than that in the normal control group (P<0.05). NT-proBNP had a negative correlation with LVEF (r=-0.549, P<0.001). The AUC of NT-proBNP in combination with LVEF for predicting cardiotoxicity in our patient was 0.898(95%CI:0.829-0.966), higher than the AUC of NT-proBNP of 0.780 (95% CI: 0.660-0.901) and LVEF of 0.675 (95% CI: 0.526-0.823). Conclusion: NT-proBNP combined with echocardiography has clinical significance in the detection of anthracyclines-induced cardiotoxicity, and it can detect early myocardial injury induced by anthracyclines, with early prediction value. It is important to protect heart function and judge prognosis.